The Jurassic of Denmark and Greenland: Shallow marine syn-rift sedimentation: Middle Jurassic Pelion Formation, Jameson Land, East Greenland - Engkilde, Michael (Geological Survey of Denmark and Greenland, 2003)
The Middle Jurassic Pelion Formation – Fossilbjerget Formation couplet of Jameson Land, East Greenland, is a well-exposed example of the Middle Jurassic inshore–offshore successions characteristicof the rifted seaways in the Northwest European – North Atlantic region. Early Jurassic deposition took place under relatively quiet tectonic conditions following Late Permian – earliest Triassic and Early Triassic rift phases and the Lower Jurassic stratal package shows an overall layer-cake geometry. A long-term extensional phase was initiated in Middle Jurassic (Late Bajocian) time, culminated in the Late Jurassic (Kimmeridgian–Volgian), and petered out in the earliest Cretaceous (Valanginian). The Upper Bajocian – Middle Callovian early-rift succession comprises shallow marine sandstones of the Pelion Formation and correlative offshore siltstones of theFossilbjerget Formation. Deposition was initiated by southwards progradation of shallow marine sands of the Pelion Formation in the Late Bajocian followed by major backstepping in Bathonian–Callovian times and drowning of the sandy depositional system in the Middle–Late Callovian. Six facies associations are recognised in the Pelion–Fossilbjerget couplet, representing estuarine, shoreface, offshore transition zone and offshore environments. The north–southtrendingaxis of the Jameson Land Basin had a low inclination, and deposition was sensitive to even small changes in relative sea level which caused the shorelines to advance or retreat over tens to several hundreds of kilometres. Eight composite sequences, termed P1–P8, are recognised and are subdivided into a total of 28 depositional sequences. The duration of the two orders of sequences was about 1–2 Ma and 360,000 years, respectively. The Upper Bajocian P1–2 sequencesinclude the most basinally positioned shallow marine sandstones, deposited during major sealevel lowstands. The lowstands were terminated by significant marine flooding events, during which sandstone deposition was restricted to northern, more ...